Konsep Percaya Diri Perspektif Al-Qur'an - Mustofa, Ahmad; Arisandi, Yusuf (Al-Jadwa: Jurnal Studi Islam, 2021)
A phenomenon that often occurs among the general public and students in particular, namely a lack of confidence in oneself often undermines the soul caused by a lack of knowledge about religion, we often see in schools students who attend school drive cars or motorbikes, they are more confident than those who use bicycles and those who take public transportation. More expensive shoes, changing bags are often a measure for students that can affect their self-confidence. From this research it can be understood that self-confidence in the Qur'an has its starting point from the noble conception of human beings, namely as the Khalifah of Allah, the best of creatures and creatures with free will. The concept of self-confidence in the Qur'an begins with having a clear self-concept of physical characteristics, traits, hobbies, strengths, weaknesses and knowing the obligations that must be carried out according to position. Then, after having a clear self-concept that the individual is a Muslim who has unique physical characteristics, traits and characteristics he must; Think positively about yourself, the situation and the environment around you. After that, every human being must believe that he has the potential given by Allah as the best chosen creature that He has created. This belief, it is not enough if only belief without action proves all of that, but is proven by action (faith and charity).